Pendekatan Life Cycle Assessment untuk Mengendalikan Dampak Pemeliharaan Vegetasi di Taman Kota 1 Bumi Serpong Damai, Kota Tangerang Selatan - Rachmad Hermawan; Luthfia Ainur Rahma; Eva Rachmawati (Jurnal Penelitian Pendidikan IPA, 2025)
Maintaining vegetation can contribute to environmental impacts by producing exhaust gases and chemical residues. Therefore, to control it, it is necessary to trace impacts using the life cycle assessment approach. The aim of this research is to inventory inputs and outputs, calculate the magnitude of the impacts caused, and formulate recommendations scenarios for controlling environmental impacts from maintaining vegetation in City Park 1 BSD. Vegetation maintenance stages are identified based on the type of input and amount of output which is calculated using the basic formula: Emissions = activity data x emission factor. Vegetation maintenance has inputs in the form of petrol, diesel, electrical energy, manure, pearl fertilizer, curacron, furadan, dry leaves, and felled trees, while the output produced is CO2, N2O, CH4, SO2, NO2, NO3, NH3, and PO43-. Acidification emissions resulting have the highest value with hotspots in the form of electricity use and watering tankers. Impact control that can be done is reducing the use of watering tankers, reducing the use of blower machines, and composting dry leaves resulting from sweeping. The life cycle assessment approach can be used as a learning resource to strengthen environmental science education